Initial response in HRI - a case study on evaluation of child with autism spectrum disorders interacting with a humanoid robot NAO. - Shamsuddin, Syamimi; Yussof, Hanafiah; Ismail, Luthffi Idzhar; Mohamed, Salina; Hanapiah, Fazah Akhtar; Zaharid, Nur Ismarrubie (Elsevier, 2012)

(untitled)
The evolution of human-robot interaction (HRI) is now expanding its wings to aid children with Autism Spectrum Disorders (ASD) in areas of socialization, communication and playful behavior through robot-based intervention. Herein we present our holistic, longstanding goal to contribute to the lives of children with ASD; who suffer a lifelong developmental disability. The purpose of this paper is to elaborate on a case study in our pilot experiment where a child with ASD is exposed to the humanoid robot NAO in order to gauge his initial response and behavior in the presence of a robot. NAO robot is the chosen robotic agent as it is a commercially available humanoid with simpler in appearance compared to real humans, thus appears more approachable to children with ASD. The pilot procedures involve the robot executing basic, simple components of interaction through a series of 5 different modules. In this study, the principal results show that the basic HRI carried out by the robot is able to suppress the child’s autistic behavior during the child-robot interaction. Also, more eye contact is observed between the child and robot compared to the child with his teacher during regular class session. Relating this to the child’s IQ which falls in the moderate category, it is suggested that children with ASD in the same IQ group will be receptive to robot-based intervention even in the first interaction session. Hence, it can be concluded that the humanoid robot NAO has potential to serve as a platform to support and initiate interaction in children with ASD.